❤❤ Good Afternoon Brainlest Guys ❤❤
®®®®®®®®®®®®®®®®®®®®®®®
⭐ Need of Step wise answer ⭐
✍✍ Solve the following pair of linear equation by the substitution method ;-
❤ 0.2x + 0.3y = 1.3
0.4x + 0.5y = 2.3
®®®®®®®®®®®®®®®®®®®®®®®®®®®®
Answers
Answered by
1
Hello Friend,
0.2x+0.3y=1.3
(0.2x+0.3y)×10=1.3×10
2x+3y=13 ---[1]
0.4x+0.5y=2.3
(0.4x+0.5y)5=2.3×5
2x+2.5y=11.5 ---[2]
Eq. [1]-[2]
2x+3y-2x-2.5y=13-11.5
0.5y=1.5
5y=15
y=3
x=(13-3y)/2=(13-3×3)/2=2
hope it helps.
joshimishi33:
hi dear brainlestuser
Answered by
3
Hi ,
0.2x + 0.3y = 1.3
multiply 10 both sides of the equation.
2x + 3y = 13
=> 2x = 13 - 3y
=> x = ( 13 - 3y )/2 -----( 1 )
0.4x + 0.5y = 2.3
=> 10( 0.4x + 0.5y ) = 10 × 2.3
=> 4x + 5y = 23 -----( 2 )
substitute x = ( 13 - 3y )/2 in
equation ( 2 ), we get
4(13 - 3y)/2 + 5y = 23
=> 2( 13 - 3y ) + 5y = 23
=> 26 - 6y + 5y = 23
=> - y = 23 - 26
=> -y = -3
y = 3
Substitute y = 3 in equation ( 1 ), we get
x = ( 13 - 3 × 3 )/2
x = ( 13 - 9 )/2
x = 4/2
x = 2
Therefore ,
x = 2 , y = 3
I hope this helps you.
: )
0.2x + 0.3y = 1.3
multiply 10 both sides of the equation.
2x + 3y = 13
=> 2x = 13 - 3y
=> x = ( 13 - 3y )/2 -----( 1 )
0.4x + 0.5y = 2.3
=> 10( 0.4x + 0.5y ) = 10 × 2.3
=> 4x + 5y = 23 -----( 2 )
substitute x = ( 13 - 3y )/2 in
equation ( 2 ), we get
4(13 - 3y)/2 + 5y = 23
=> 2( 13 - 3y ) + 5y = 23
=> 26 - 6y + 5y = 23
=> - y = 23 - 26
=> -y = -3
y = 3
Substitute y = 3 in equation ( 1 ), we get
x = ( 13 - 3 × 3 )/2
x = ( 13 - 9 )/2
x = 4/2
x = 2
Therefore ,
x = 2 , y = 3
I hope this helps you.
: )
Similar questions